ARCHIVAL MEANING: MATERIALITY, DIGITIZATION, AND THE NINETEENTH-CENTURY PHOTOGRAPH. - Volpe, Andrea L. (Afterimage)
The article reviews two exhibitions presented at the Peabody Museum of Archaeology and Ethnology, "A Good Type: Tourism and Science in Early Japanese Photography" from October 2007-April 2008 and "Fragile Memories: Images of Archaeology and Community at Copán, 1891-1900" from June 2008-March 2009.